Pendidikan Karakter Islami dalam Novel “Tentang Kamu” - Gofarun Gofarun; Abdul Munif (Prodi PAI STIT Raden Santri Gresik, 2024)
Today's character education shows a decline in student character. This is due to the rapid advancement of technology and the absence of comprehensive character education using new methods. This study aims to analyze and reveal the values ​​of character education contained in the novel